New Methods to Evaluate Endothelial Function: Non-invasive Method of Evaluating Endothelial Function in Humans - Masayoshi Hashimoto; Yoshitomo Miyamoto; Yasuaki Matsuda; Hozuka Akita (Elsevier, 2003)
ABSTRACT: Evidence has accumulated that impairment of vascular endothelial function is the initial step in the development of atherosclerosis. One important finding is impairment of the release of endothelium-dependent relaxing factor, which is now thought to be nitric oxide or its related substances, from endothelial cells. Flow-mediated dilatation has been known to be endothelium-dependent, and this can be detected during reactive hyperemia by high-resolution ultrasound in superficial arteries. Several coronary risk factors have been reported to be significantly related with decreased flow-mediated dilatation. We studied the association between the accumulation of coronary risk factors (hyperlipidemia, diabetes mellitus, hypertension, and current smoking habitus) and vascular endothelial function. The lower incidence of atherosclerosis in women before the menopause than that in men is an established epidemiological observation. Short-term estrogen therapy improves endothelial function in postmenopausal women. However, there are few reports on its long-term effects on endothelial function. Furthermore, we determined whether a reduced dosage of estrogen may maintain its beneficial effects. A similar improvement was also observed while women were on hormone replacement therapy even at the reduced dosage. Our results indicate that even at half the dose of estrogen, hormone replacement therapy may improve endothelial function in postmenopausal women.